Analisa Penerapan Prinsip Syariah dalam Asuransi - Teguh Suripto; Abdullah Salam (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
In recent years, we have heard and seen many economic activities based on Islamic law or Sharia law. These activities are related to the production process in the service industry. So it appears Sharia Business Unit (UUS), such as Islamic Banking, Sharia Insurance, Sharia Pawnshops, Sharia Leasing, even up to syariah tourism. This is certainly very reasonable, because the rationality and social level of human life undergo many changes, from the level of social and economic life that has freedom, to a new economic level that requires religious values. The Islamic economic system has different characteristics from conventional economics. Islamic economics is a fair and thorough system and seeks to ensure that wealth is not collected only to one group, but spread throughout society. (Afzalur Rahman, 1996: 11). One of Sharia financial institutions that can apply the sharia principles is Sharia Insurance. This research will try to analyze the principles of sharia in insurance, using qualitative descriptive method that is describing the object of research by using literature study that comes from the relevant book or journal. The result of the research shows that there are 8 principles in Takaful Insurance which become the guideline of implementation, that is Tawheed (Ketaqwaan), Justice, Not Dzalim, At Tawaun (please help), Amanah, Ridha, Khitmah (good service), and free from gharar element, maisir, and usury. In practice many sharia entities have been implementing sharia principles well although there are still some shortcomings in Takaful insurance, for example in research that has been done by Erza Armas hardi, 2015 obtained the result that Takaful insurance has not touched the bottom of society group (grass root).Keywords :  Sharia Insurance, Sharia Principles, Sharia Entity, Tabarru